The Racial Disparities in the Epidemic of Metabolic Syndrome With Increased Age: A Study From 28,049 Chinese and American Adults - Zhang, Ruiying; Sun, Jie; Wang, Chaofan; Wang, Xiangtuo; Zhao, Pei; Yuan, Yucong; Ai, Hu; Zhou, Qi (Frontiers in Public Health, 2022)
Background: Previous studies have revealed ethnic disparities in the prevalence of metabolic syndrome (MetS); however, the literature regarding aging-related patterns of disparities in MetS and its components remains limited. Methods: This cross-sectional study recruited 28,049 subjects, consisting of one Chinese race and three American races, 18–85 years of age, from the National Health and Nutrition Examination Survey (NHANES, 1999–2018) of the United States, and the Guangdong Gut Microbiome Project (GGMP, 2018) of China. MetS was defined in accordance with the National Cholesterol Education Program Adult Treatment Panel III. A modified sliding-window-based algorithm was used to depict the trajectories of the prevalence of MetS with increased age. Logistic regression analysis was performed to investigate associations between MetS and its components. Results: The prevalence of MetS increased non-linearly with age, with growth speed reaching its maximum at approximately 40–50 years. Chinese subjects exhibited a lower prevalence of MetS than non-Hispanic whites, non-Hispanic blacks, and Mexican Americans in all age groups. The two most prevalent components in Chinese subjects were reduced high-density lipoprotein cholesterol levels (42.0%) and elevated blood pressure (49.5%), and elevated triglyceride levels (36.3%–49.5%) and abdominal obesity (55.8%-55.9%) in Americans. Before 40 years of age, the top two MetS-associated components were abdominal obesity and elevated triglyceride levels in all races, while after 40 years, the prominent associations between MetS and its components varied among the different races and age groups. Conclusions: Although racial disparities in the epidemic of MetS varied with increased age, abdominal obesity and elevated triglyceride levels were the top two MetS-associated components in all younger adults of different races.